2014
DOI: 10.1158/1538-7445.am2014-4748
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 4748: Discovery of JNJ-42756493, a potent fibroblast growth factor receptor (FGFR) inhibitor using a fragment based approach

Abstract: Fibroblast growth factors (FGFs) and their receptors (FGFR1 through 4) regulate a variety of key cellular processes, including proliferation, migration, survival, and differentiationa. Aberrant activation of FGF/FGFR is strongly implicated in oncogenic signalling in many tumor types. This has stimulated the development of a number of FGFR inhibitors, with diverse kinase inhibition and pharmacological profiles that are currently being evaluated in clinical studies. We conducted a fragment screeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Among these, inhibitors AZD4547, BGJ398 and JNJ42756493, were selected because they have been shown to effectively inhibit FGFR1 kinase in biochemical assays [1922]. However, since each inhibitor has been investigated in isolation, in different model systems, it has not been possible to determine the relative efficacy and specificity of these drugs in inhibiting FGFR1 activity and related phenotypes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, inhibitors AZD4547, BGJ398 and JNJ42756493, were selected because they have been shown to effectively inhibit FGFR1 kinase in biochemical assays [1922]. However, since each inhibitor has been investigated in isolation, in different model systems, it has not been possible to determine the relative efficacy and specificity of these drugs in inhibiting FGFR1 activity and related phenotypes.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, several additional, more specific pan-FGFR inhibitors have been developed, such as AZD4547 [19], BGJ398 [20, 21], JNJ42756493 [22] and LY2874455 [23], in addition to multi-target inhibitors such as ponatinib (also known as AP24534) [24], TKI258 [25] and E3810 [26]. Ponatinib (Iclusig ® ) is an FDA approved drug for the treatment of chronic myeloid leukemia (CML) and Philadelphia chromosome–positive acute lymphoblastic leukemia (ALL).…”
Section: Introductionmentioning
confidence: 99%
“…Ponatinib, which was originally developed to target the BCR‐ABL, T315I mutation, was shown to also inhibit FGFR1 at low concentrations and is particularly effective against FGFR1 driven neoplasms but also inhibits other kinases such as KIT and FLT3. More recently, however, more specific FGFR inhibitors such as ADZ4547, JNJ42756493 and BGJ398 have been developed. We have evaluated the relative efficiency of these different FGFR1 inhibitors in suppressing growth of leukemic cells lines expressing chimeric FGFR1 kinases and demonstrated that they are highly effective in suppressing in vitro growth at nanomolar concentrations, and have demonstrated the effectiveness of BGJ398 against SCLL syndromic and de novo FGFR1 overexpressing AML in vivo , paving the way for clinical trials using FGFR1 inhibitors in subtypes of AML overexpressing FGFR1.…”
mentioning
confidence: 99%
“…As many of the FGFR inhibitors are nonselective, with many inhibiting VEGFR and PDGFR (discussed above), the focus of this section is limited to selective FGFR inhibitors that have entered clinical development (Table ). Those inhibitors include AZD4547 ( 40 ), infigratinib ( 41 ), erdafitinib ( 42 ), CH5183284 ( 43 ), and ARQ 087 (structure not available). Of these, infigratinib has advanced to clinical studies in patients with GBM .…”
Section: Fgfrmentioning
confidence: 99%